2018
DOI: 10.1088/1757-899x/349/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Simultant encapsulation of vitamin C and beta-carotene in sesame (Sesamum indicum l.) liposomes

Abstract: Abstract. In this study sesame liposomes were used to encapsulate both vitamin C and betacarotene simultaneously. Liposomes were prepared with addition of cholesterol. The encapsulation efficiency (EE) of sesame liposomes for vitamin C in the present of beta-carotene was 77%. The addition of cholesterol increased the encapsulation efficiency. The highest encapsulation efficiency was 89% obtained in liposomes with 10% and 20% cholesterol. Contrary to that, the highest beta-carotene encapsulation efficiency of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…The optimized liposome did not contain cholesterol. Hudiyanti et al [ 57 ] showed that the encapsulation efficiency of β-carotene decreased from 79% to 60% with 0% and 40% cholesterol, respectively, since both molecules competed to be inside the vesicle bilayer. Quinine entrapment by liposomes was also affected by the cholesterol incorporation in the system, where 40% cholesterol produced an EE ranging from 5.6% to 84.07%; decreasing the cholesterol by 10% increased the EE to 88% [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The optimized liposome did not contain cholesterol. Hudiyanti et al [ 57 ] showed that the encapsulation efficiency of β-carotene decreased from 79% to 60% with 0% and 40% cholesterol, respectively, since both molecules competed to be inside the vesicle bilayer. Quinine entrapment by liposomes was also affected by the cholesterol incorporation in the system, where 40% cholesterol produced an EE ranging from 5.6% to 84.07%; decreasing the cholesterol by 10% increased the EE to 88% [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The liposomal applications have been studied extensively in dairy products (Laridi et al 2003), in terms of stability of the food components against degradation (Hudiyanti et al 2018) and enhanced delivery action of the antimicrobial peptides (Paula et al 2019). In cheese-making, liposome encapsulated enzymes reduced the cheese ripening time up to 50%.…”
Section: Food Processingmentioning
confidence: 99%
“…In liquid food products, beta carotene has a low chemical stability and low bioavailability due to its hydrophobicity. Introducing liposome techniques may improve the solubility of beta carotene by incorporation of dried phospholipid particles using spray drying (Toniazzo et al 2014) and active loading techniques (Hudiyanti et al 2018) in sesame based liposome ingredients.…”
Section: Curcuminmentioning
confidence: 99%
“…Adding cholesterol to the liposome assembly process makes it possible to maintain and even increase the membrane's stability. An adequate amount of cholesterol in liposomes can decrease membrane permeability and increase membrane stifness, enhancing the membrane's stability [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Te liposomes used in drug delivery systems have been studied experimentally and computationally for polar and nonpolar drugs [12][13][14][15][16][17][18][19][20][21]. Computational studies on issues related to experimental studies can confrm or complement relevant data or information acquired experimentally or even simulate trials to conduct future experiments more efciently.…”
Section: Introductionmentioning
confidence: 99%